Wordwall-Based Pie Learning Media Innovation in MI Miftahul Khoir - Maulindini, Adelya; Yusuf, Achmad (Yayasan Rahmat Islamiyah, 2025)
This research aims to discuss the innovation of Islamic Religious Education (PAI) learning media based on Wordwall which is already familiar to be used in the learning process. Using a descriptive qualitative approach with a case study type, this study involved Islamic religious education subject teachers to find out the innovation and implementation in the teaching and learning process. The results of the study show that the use of innovative learning media using Wordwall makes students more active and encourages students to think critically in the learning process. The steps in the use of Wordwall have also been discussed in it starting from the definition, how to implement it to the disadvantages and advantages of Wordwall. This research emphasizes the use of technological tools to help visualize abstract and difficult-to-understand things by utilizing technological developments. The implications of these findings are about the need for the use of digital media to continue to support the learning process so that it continues to grow and be able to adapt to the development of the times in the optimal use of technology.